KINERJA RANTAI PASOK FILLET IKAN PATIN BEKU DI DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR (SUATU KASUS PADA CV. GRAHA PRATAMA FISH) - Fauziah Fauziah; Sisca Vaulina (Jurnal Agribisnis Indonesia, 2020)
Koto Mesjid village is familiar with named “Kampung Patin”, one of pangasius fish cultivator is CV. Graha Pratama Fish. The purpose this research were to analyze value added of frozen pangasius fish fillets, to know person of supply chain in frozen pangasius fish fillets, to know circle supply chain in frozen pangasius fish fillets and to analyze performance of supply chain in frozen pangasius fish fillets. Using case study, data was analyzed by Model DEA-CCR. This result evidence that value added obtained is IDR 6,391 per Kg. The person of supply chain in frozen pangasius fish fillets are supplier of pangasius fish raw material, entrepreneur of frozen pangasius fish fillets and customer. The circle supply chain consists of product flow, financial flow and information flow. The performance SCOR of frozen pangasius fish fillets generally is performing well. DEA in frozen pangasius fish fillets has 5 suppliers that achieve 100% efficiency in green condition, from December 2018 to January 2019. While the frozen pangasius fish fillets supply chain achieve 100% efficiency in green condition obtained in January 2019. Cash-to-cash cycle time sensitivity are the most influential variable on efficiency value of the pangasius fish supply chain and there is no sensitivity value that most influences the efficiency of frozen pangasius fish fillets. Recommendations for improvement of the total potential improvement namely variable input cash-to-cash cycle time 98,78% and input costs 1,22%.